UMP towards Smart Campus - Mimi Rabita, Abdul Wahit (2021)
PUTRAJAYA, 12 December 2021 – Universiti Malaysia Pahang aims to become a smart campus and the implementation of this initiative is in line with government’s aspiration in strengthening digital government agenda in this country.